Self-protection of individual CD4+ T cells against R5 HIV-1 infection by the synthesis of anti-viral CCR5 ligands. - Yongjun Guan; Sayed Abdelwahab; Roberta Kamin-Lewis; Anthony L DeVico; George K Lewis (PLoS ONE, 2008)
It is well established that paracrine secretion of anti-viral CCR5 ligands by CD8+ and CD4+ T cells can block the infection of activated CD4+ T cells by R5 and dual-tropic isolates of HIV-1. By contrast, because CD4+ T cells can be infected by HIV-1 and at least some subsets secrete anti-viral CCR5 ligands, it is possible that these ligands protect against HIV-1 via autocrine as well as paracrine pathways. Here we use a model primary CD4+ T cell response in vitro to show that individual CD4+ T cells that secrete anti-viral CCR5 ligands are 'self-protected' against infection with R5 but not X4 strains of HIV-1. This protection is selective for CD4+ T cells that secrete anti-viral CCR5 ligands in that activated CD4+ T cells in the same cultures remain infectable with R5 HIV-1. These data are most consistent with an autocrine pathway of protection in this system and indicate a previously unappreciated selective pressure on the emergence of viral variants and CD4+ T cell phenotypes during HIV-1 infection.